Size-controlled synthesis of gold nanoparticles by ultrafine bubbles and pulsed ultrasound. (18th May 2020) - Yasuda, Keiji; Sato, Tomofumi; Asakura, Yoshiyuki
Graphical abstract: Highlights: Pulsed ultrasound and ultrafine bubbles controlled the size of gold nanoparticles. The size of gold nanoparticles decreased with increasing ultrafine bubbles. The size of gold nanoparticle varied with gaseous species inside ultrafine bubbles. Ultrafine bubbles improved colloid stability of gold nanoparticles. The size of gold nanoparticles increased with increasing the pulse-off time. Abstract: Size-controlled gold nanoparticles (AuNPs) were synthesized by ultrasonic irradiation of HAuCl4 aqueous solutions with the aid of ultrafine bubbles (UFBs) in the absence of any capping and reducing agents. Upon addition of air-UFBs, the mean diameter of the spherical AuNPs decreased. This result was attributed to the sonochemical reduction of gold ions in aqueous solution being accelerated by the UFBs. Moreover, the AuNPs were stable in a solution containing UFBs because AuNPs electrostatically adsorbed onto UFBs, whose lifetime in water was very long. Compared with the mean diameter of AuNPs synthesized with argon-, nitrogen- and oxygen-UFBs, that of AuNPs synthesized with air-UFBs was smaller. Pulsed ultrasound delivered with the same time-averaged power as continuous-wave irradiation further decreased the mean diameter of the AuNPs. Size-controlled synthesis of AuNPs without the use of a capping or reducing agent was successful through optimization of the number air-UFBs and the pulsed ultrasound conditions.